PENGARUH PEMBERIAN SUSU TERHADAP INDEKS MASSA TUBUH DAN KEPADATAN TULANG PUNGGUNG REMAJA PRIA - Suryono Suryono; Ali Khomsan; Budi Setiawan; Drajat Martianto; Dadang Sukandar (Jurnal Gizi dan Pangan, 2007)
Milk is the best source of calcium and many studies suggest that adolescence who drink milk or eat other dairy foods have stronger bones and better nutritional status. The objectives of this study were to determine effect of high calcium and fresh milk on nutritional status and bone density. Variables measured in this study were body mass index and bone density of trunk. Samples were 55 adolescent boys aged 17 to 19 years old (students of TPB IPB). The study was conducted at TPB IPB dormitory during four months. The design of this study was nested randomized design with two factors. Two kinds of milk (fresh milk and high calcium milk) and 3 levels of volume (250 ml, 500 ml, and 750 ml) were used. Results of the study indicated that high calcium milk consumption was able to increase body mass index and bone density of trunk. It was found that high calcium consumption showed very highly significant effect (P<0.01) on bone density of trunk. Calcium from high calcium milk showed very highly significant effect (P<0.01) on body mass index. Based on general linear model equation, bone density of trunk can be estimated by high calcium milk consumption.